Code of Ethics Violations Due to Constitutional Court Decision Number 90/PUU-XXI/2023 Towards the Dynamics of the 2024 Election in Indonesia - Larasati, Herwinda; Aeni, Intan Nur; Febrianti, Selma Savita; Safitri, Theona (LPPM Universitas Harapan Bangsa, 2024)
The Constitutional Court's (MK) Decision No. 90/PUU-XXI/2023 has sparked widespread debate regarding code of ethics violations in the context of Indonesia's 2024 general elections. Some consider this decision, which affects election regulations and mechanisms, as a deviation from the ethical principles that should be upheld in democratic processes. This research aims to analyze the impact of the decision on the dynamics of the 2024 elections, focusing on the aspects of code of ethics violations that have emerged. The method used is document study and normative juridical analysis, which includes an assessment of the Constitutional Court's Decision, related election regulations, and legal and ethical literature. The results showed strong indications of violations of the code of ethics by several parties involved, both in terms of technical implementation and in the context of political campaigns. The Constitutional Court's Decision also raises new challenges in maintaining the integrity and fairness of elections and affects public confidence in the democratic process. In conclusion, concrete steps are needed to strengthen oversight mechanisms and enforce the code of conduct to ensure that the 2024 elections occur pretty and transparently and respect the underlying ethical principles.